FACTOR THAT IS RELATED TO PALLIATIVE CARE ON PATIENT TERMINAL AT SITI KHADIJAH ISLAMIC HOSPITAL PALEMBANG IN 2015 - Mardiah; Mina Marlina (STIK SITI KHADIJAH PALEMBANG, 2017)
From result in medical record at Siti Khadijah Islamic Hospital Palembang in 2013 the died patient of amount 501 people while on 2014 in rise 610 people caused by terminal illness. The patient terminal have to get his palliative care that is to relieve symptoms of disease and improve the quality of life for the patient as well as the handling of pain and other issues such as physical, psychosocial and spiritual.The purpose of this research is to know the relationship between physical factors, social support, and spiritual support to palliative care to patients at Siti Khadijah Islamic Hospital Palembang. The method of this is quantitative with survey analytic through cross sectional approach. The total sample of this study 38 respondents by using the total population. The questionnaire was used to collect the data. The Chi-Square statistic was used in this study, analysis the data used by univariate and bivariate. From statistic test found that there are a correlation among physical factors in palliative care with p value 0,005 < α (0,05), a correlation among social support in palliative care with p value 0,018 < α (0,05), a correlation among spiritual support in palliative care with p value 0,028 < α (0,05). To Siti Khadijah Islamic Hospital Palembang hope that inputed and judgment in do measure leadership care most to patients terminal.